Suprasellar granular cell tumor: A rare case report - Parmar , Vipal Hasmukhbhai; Parikh, Prashant Mahendrabhai; Mehta, Bhavana Asit; Shah, Sandip Chandrakant; Murnal, Ankita Girish (Eastern Journal of Medical Sciences, 2024)
Granular cell tumor (GCT) originating from the sellar and suprasellar regions, specifically from the neurohypophysis, is a rare neoplasm. Symptomatic GCT of the neurohypophysis is exceedingly rare, being <70 cases described so far. GCTs predominantly exhibit benign behavior, while the malignancy rate remains at 2%. Imaging is quite unspecific and diagnosis is difficult to establish preoperatively. Histopathology and immunohistochemistry serve as the definitive diagnostic approach for GCTs and help in distinguishing GCT from other pituitary tumors, including pituitary adenoma, pituicytoma, and spindle cell oncocytoma. These tumors are resistant to radiotherapy and chemotherapy, necessitating surgical resection as the primary treatment modality. Due to the potential absence of distinct tumor masses and local tissue infiltration by tumor cells, complete excision is crucial, with resection extent extending beyond areas of infiltration. Here, we present a rare case of GCT originating from the posterior pituitary in the suprasellar region. On immunohistochemistry, tumor cells expressed diffusely thyroid transcription factor-1, S-100 protein, and vimentin confirming the diagnosis of supra-sellar GCT. The reported case is noteworthy for the rarity of the clinicopathological entity.